2023
DOI: 10.1021/acs.joc.3c00084
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Enantioselectivity Relationship (SER) Study of Cinchona Alkaloid Chlorocyclization Catalysts

Abstract: Various structural elements of the Cinchona alkaloid dimers are interrogated to establish a structure–enantioselectivity relationship (SER) in three different halocyclization reactions. SER for chlorocyclizations of a 1,1-disubstituted alkenoic acid, a 1,1-disubstituted alkeneamide, and a trans-1,2-disubstituted alkeneamide showed variable sensitivities to linker rigidity and polarity, aspects of the alkaloid structure, and the presence of two or only one alkaloid side group defining the catalyst pocket. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The HSQC and NOESY spectra are reported in the Supporting Information (Figures S47–S49), and the NOE correlations of the methine proton H 1 with other protons of the quinoline and quinuclidine moieties were identified. According to already reported literature, , rotations about C8–C9, C9–O, and C9–C16 bonds can lead to conformational arrangements in which the quinuclidine nitrogen points far away from the quinoline ring, and that is more suited for its interaction with acidic substrates. Graphical representation of dimeric (DHQD) 2 PHAL clearly showed that CSA provides two well-defined chiral pockets, which consist of the aromatic phthalazine plane, chiral quinuclidine ring, and aromatic quinoline plane, respectively.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The HSQC and NOESY spectra are reported in the Supporting Information (Figures S47–S49), and the NOE correlations of the methine proton H 1 with other protons of the quinoline and quinuclidine moieties were identified. According to already reported literature, , rotations about C8–C9, C9–O, and C9–C16 bonds can lead to conformational arrangements in which the quinuclidine nitrogen points far away from the quinoline ring, and that is more suited for its interaction with acidic substrates. Graphical representation of dimeric (DHQD) 2 PHAL clearly showed that CSA provides two well-defined chiral pockets, which consist of the aromatic phthalazine plane, chiral quinuclidine ring, and aromatic quinoline plane, respectively.…”
Section: Resultsmentioning
confidence: 81%
“…They have played an important role in asymmetric syntheses over the past many years because they are inexpensive, readily available, stable, and easily recoverable. As representative chiral ligands and chiral organocatalysts, dimeric Cinchona alkaloids via an ether bond with heterocyclic linkers have been widely used in catalytic asymmetric reactions such as asymmetric halogenations, Sharpless dihydroxylation, sulfenylation, allylic alkylation, and Michael addition. They have also been used to form C–C bonds, C–N bonds, and C–O bonds. As we know, the key step in chiral recognition is the formation of in situ diastereoisomeric complexes between enantiomers and a suitable chiral host. It is widely accepted that an effective chiral recognition model should involve multipoint interactions between the host and the guest, with the strongest and most effective interactions being electrostatic (Coulomb), hydrogen bonds, steric hindrance, π–π, and ion–dipole interactions .…”
Section: Introductionmentioning
confidence: 99%